EFEK SKOR ESG PADA KAPITALISASI PASAR PERUSAHAAN DALAM INDEX ESG LEADERS INDONESIA - Nugroho, Emanuel Yakobus Prasetyo; Sumani, Sumani (Universitas Katolik Indonesia Atma Jaya, 2025)
ESG is a concept that prioritizes sustainable development, investment, and company operations using three criteria—environmental, social, and governance. Businesses with strong ESG policies typically do better over the long run. Revenue, net profit, growth, and a greater market valuation—reflected in market capitalization—can all be indicators of improved long-term performance. This study examines the relationship between ESG scores and market capitalization for 17 businesses included in the Indonesian ESG Leaders Index (March 15-September 19, 2023) using firm value as an intervening variable. Multiple linear regression analysis was employed as the data analysis strategy. The study’s results, which were obtained by regression analysis with IBM SPSS 29, demonstrated that ESG scores had no discernible impact on market capitalization as measured by business value overall. .